Pengaruh Kompetensi Pustakawan, Kinerja Pustakawan terhadap Kualitas Pelayanan Perpustakaan di IAIN Curup - Ari Mariani; Saidil Mustar; Rahmat Iswanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to influence librarian competence and librarian performance on the quality of IAIN Curup library services. The type of research used in this research is quantitative research. Quantitative research is an approach to testing objective theories by testing the relationships between variables. The population in this research is the academic community at IAIN Curup, such as students entering 2021. The population of students entering 2021 at IAIN Curup is 577 students. The sample in this research was 85 students. The results of the research show that the level of competence of librarians influences the quality of IAIN Curup library services with a significant value of 0.024. Meanwhile, the performance of librarians has no effect on the quality of IAIN Curup library services with a significant value of 0.001. The influence of librarian competence and librarian performance simultaneously (together) influences the quality of IAIN Curup library services, with F count 148.189 > F table 3.11 and a significance level of 0.001 < 0.05, meaning that H0 is rejected and Ha is accepted. The conclusion is that the independent variables in the form of librarian competence and librarian performance simultaneously or jointly influence the dependent variable, namely the quality of IAIN Curup library services. Keywords: Librarian Competence, Librarian Performance, Library Service Quality, IAIN Curup